In situ Tribo-Fluorination for Oil-Less Hermetic Compressor Applications - Borges, Gabriel; Salvaro, Diego; Binder, Roberto; Binder, Cristiano; Klein, Aloisio N.; de Mello, Jose D. B. (Frontiers in Mechanical Engineering, 2021)
This paper overviews a multidisciplinary approach to develop a regular hermetic compressor (oil-lubricated, with several rotating parts) into an oil-less, linear motion, innovative compressor with improved efficiency, versatility, and sustainability. This involved developing surface engineering processes and combining purpose-oriented phases applied to soft substrates. Particular emphasis is given to the in situ fluorination of the tribolayer formed in the piston-cylinder tribo-pair. Although chlorinated halocarbons (CFC) are efficient refrigerants from a thermodynamic point of view, they do have serious environmental implications that have forced the refrigeration industry to switch to more environmentally friendly hydrofluorocarbon (HFC) based refrigerants. The first and most successful alternative to the CFCs was tetrafluorocarbon, particularly tetrafluoroethane (CF3CH2F), aka R134a refrigerant. Due to miscibility issues, R134a is limited to applications with fully synthetic lubricants, which associated with the need for more energy-efficient compressors, implying in downsizing, smaller clearances, and increased speeds led to the development of a new generation of oil-free hermetic compressors, the Wisemotion® , the first, and until now, unique, oil-free hermetic compressor on the world market. In this context different types of multi-layers, their thickness, substrate material, processing routes, etc., have been studied and optimized. Si-rich hydrogenated DLC (a:C-H) presented enhanced tribological properties when tested under fluorine-rich atmospheres, and semi-industrial scale tests have been carried out to understand this point further. A homemade tribological emulator was developed allowing close-to-real tribo-pair, atmosphere, and imposed mechanical conditions used in an oil-free commercial hermetic compressor. The tests were carried under different stroke frequencies (5, 20, and 40 Hz) and atmospheres (R134a, ambient air, and argon). Results showed a strong influence of both atmosphere and stroke frequencies. The friction coefficients were significantly lower ( 3.8X) for the refrigerant gas atmosphere, attributed to the fluorine and highly disordered graphitic structures rich tribolayers. Under the high frequency (40 Hz), the energy input seems to be a deterrent to the formation of stable tribolayers, and the DLC coating shatters on the first few sliding meters.